The mastery of innovation : a field guide to lean product development - Radeka, Katherine (CRC Press, 2013)
What do Ford Motor Company, Steelcase, Scania, Goodyear, Novo Nordisk, and Philips Electronics have in common? They all need to get their best ideas to market as fast as possible. They need to achieve the mastery of innovation. When these companies needed to accelerate time-to-market, get more new products to customers, and improve their ROI from investments in R & D, they turned to Lean Product Development to help them master the process of innovation. By adapting Lean ideas to their specific product development challenges, they learned how to focus innovation on the problems that would maximize.